The use of alternative medicine for pain management in modern palliative care - Ryglowski, Piotr J.; Nowak, Martyna; Kłosowska, Wiktoria; Idzik, Natalia; Gaweł-Dąbrowska, Dagmara (Medycyna Paliatywna/Palliative Medicine, 2025)
Palliative care is a specialised branch of medicine aimed at improving the quality of life for patients and their families facing chronic and often terminal diseases. To achieve this goal, healthcare providers must focus on patients’ needs, including pain management and mental, emotional, and spiritual well-being. While conventional medicine – both pharmacological and non-pharmacological treatments – plays a primary role, modern palliative care increasingly integrates complementary and alternative medicine (CAM) as part of a holistic approach to patient care. CAM includes a wide range of treatments such as aromatherapy, acupuncture, music therapy, hypnosis, meditation, and mindfulness. Despite ongoing controversy surrounding these methods, recent research indicates their potential effectiveness in holistic palliative care.